Perkembangan dan Peranan Radio Berbasis Dakwah Islamiyah - Effendy, Erwan; Rayhan, Aisyah; Harlah, Nur Aisyah; Hasibuan, M. Fauzan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Talking about da'wah and radio, we must distinguish between "radio da'wah" and "radio da'wah". Da'wah radio is a radio station whose vision, mission, and all broadcast material is about da'wah (sib of Islam). Meanwhile radio da'wah is da'wah activity on radio media. Da'wah radio is programmed to broadcast Islam. All of his programs are related to da'wah or Islamic nuances. For example, such as religious songs (nasyid and religious pop), there are no other than religious or Islamic nuances. All events including songs contain and are oriented towards Islamic da'wah. There is also da'wah radio which is "anti-music" following the argument that it is forbidden, absolutely all types of music. There were no songs played and no music broadcasts (tune) on the radio, all were "Complete" broadcasts of da'wah and word broadcasts (talk), in the form of lectures, dialogues, and the like. Keywords: Radio, Da'wah, Islam